PENJELAJAHAN SAMUDRA ORANG-ORANG EROPA - Rosmaida, Rosmaida Sinaga; Syahrani, Syahrani; Elia, Elia Br. Ginting; Hendrison, Hendrison Adipura Hasibuan; Yonathan, Yonathan Louis Pratama Lase (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Maritime exploration by European nations between the 15th and 17th centuries was driven by a number of factors, including the fall of Constantinople, which cut off overland trade routes to Asia, advances in navigational technology such as the compass and caravels, and the desire to acquire wealth (gold), glory, and spread Christianity. Portugal and Spain were the main pioneers in opening new trade routes to Asia, followed by the Netherlands and England, who continued to expand their explorations to various parts of the world. These exploration activities had a major impact, such as the establishment of international trade routes, the colonization of new regions, cultural exchange, and social and economic changes in the explored regions. This event marked the beginning of the era of globalization that has influenced modern world history.